Reactivity of Low-Valent Iron and Cobalt Complexes with Fluoroalkenes - Ghostine, Karine (Université d'Ottawa / University of Ottawa, 2018)
Fluorocarbons are versatile molecules that are used in multiple industries ranging from pharmaceuticals to refrigerants, insecticides and advanced materials. More particularly hydrofluorocarbons (HFCs) and hydrofluoroolefins (HFOs) are current replacements for ozone-depleting chlorofluorocarbons (CFCs) that were used for decades as refrigerants, propellants, solvents and blowing agents. However, syntheses of HFCs and HFOs involve energy-intensive processes and toxic compounds such as heavy metals and anhydrous HF. Development of more sustainable, energy efficient and "greener" synthesis of small fluorocarbons is needed, which draws attention to organometallic catalysis, especially with abundant, inexpensive and non-toxic transition metals. One approach to new organometallic routes to hydrofluorocarbons involves the formation and functionalization of fluorometallacycles. Previous work in the 1990’s by Baker et al. demonstrated the catalytic hydrodimerization of tetrafluoroethylene (TFE) using Ni catalysts with π-acidic phosphite ligands. They also demonstrated the hydrogenolysis of the d6 ferracyclopentane, Fe(CO)4(1,4-C4F8), 2-1, under high pressure and temperature with different additives to give mixtures of different hydrofluorocarbons. Since that time the reactivity of d8 fluorometallacyles has been extensively studied, leading to fundamental understanding and new catalytic applications. However less attention has been paid to d6 systems, the synthesis and reactivity of which are the focus of this Thesis. Following introduction and background in Chapter 1, Chapter 2 presents the synthesis and characterization of a series of new NHC-, phosphine- and nitrogen-ligand-substituted Fe(II) perfluorometallacycles derived from complex 2-1. This led to the discovery of the first example of a fluorinated metallacyclocarbene obtained from in situ Cα–F bond activation that afforded FeF(triphos)(1,4-C4F7), 2-6, (triphos = bis(2-diphenylphosphinoethyl)phenylphosphine) during the P-based linear tridentate ligand substitution reaction. [Fe(triphos)(1,4-C4F7)(NCMe)]+BPh4-, 2-7, and Fe(OTf)(triphos)(1,4-C4F7), 2-8, were derived from 2-6 by treatment with NaBPh4 in acetonitrile and Me3Si-OTf, respectively (Tf = triflate, SO2CF3). The same phenomenon was not observed with hard-donor N-based linear tridentate ligand, terpy’, (terpy’ = 4′-(4-methylphenyl)-2,2′:6′,2′′-terpyridine), presumably because of the less Lewis acidic metal center. Fluoride abstraction from Fe(terpy’)(CO)(1,4-C4F8), 2-9, by a Lewis acid, however allowed for Cα–F bond activation to give the cationic iron monocarbonyl carbene complex, [Fe(terpy’)(CO)(1,4-C4F7)]+OTf–, 2-10. Chapter 3 investigates further the reactivity of these new Fe(II) perfluorometallacycle complexes. The lack of reactivity of the mono- and di-substituted Fe carbonyl perfluorometallacycles with Lewis acids confirmed that Cα–F bond activation only occurs when there is enough π-backbonding into the Cα–F anti-bonding orbital, as π-acceptor phosphines and carbonyl ligands can compete for the metal back-bonding. Indeed, Cα–F abstraction is only observed with Fe(terpy’)(CO)(1,4-C4F8), 2-9, due to the poor acceptor ability of the nitrogen ligand. On the other hand, the lack of electron density on the metal center can cause the Fe center to act as an internal Lewis acid, promoting Cα–F migration as observed in situ during the triphos substitution reaction. These results show that d6 [Fe] perfluorometallacycles do not share similar reactivity with d8 [Ni] perfluorometallacycles. Moreover, the study of the character of the Fe=CF bonds suggests a nucleophilic carbene for 2-6, while 2-7, 2-8 and 2-10 all displayed electrophilic carbene character. Furthermore, hydrogenolysis of Fe(OTf)(triphos)(1,4-C4F7), 2-8, and [Fe(triphos)(1,4-C4F7)(NCMe)]+BPh4-, 2-7, at low pressure and room temperature, generated exclusively H(CF2)3CFH2, HFC-347pcc, and iron hydrides, confirming a previous hypothesis that attributed formation of this hydrofluoroalkane to an Fe carbene intermediate. In contrast, [Fe(terpy’)(CO)(1,4-C4F7)]+OTf–, 2-10, reacts with H2 to yield HF and an unidentified iron complex, showing that the nature of the ancillary ligands greatly influences the reactivity. Chapter 4 explores the reactivity of phosphine-substituted cobalt(I) carbonyl hydride complexes towards TFE to expand our work on d6 perfluorometallacycles. The most electron-rich ligands prevented metallacycle formation or slowed it down possibly due to strong π-backbonding into the CO ligands, making it harder to generate an open coordination site. Indeed, a mixture of the Co-tetrafluoroethyl complex, derived from insertion of TFE into Co–H, and the zerovalent dimer/hydrogenated TFE products, derived from the reaction of the Co–H with the 16e- CoLn(CO)3-n(CF2CF2H) intermediate, were obtained with the bulkiest ligands, CoH(dcppe)(CO)2 and CoH(Pcp3)(CO)3 (dcppe = 1,2-bis(dicyclopentylphosphino)ethane, cp = cyclopentyl). With the slightly less bulky PiBu3 ligand, further reactivity of the insertion product with TFE slowly formed a d6 metallacycle hydride complex. In contrast, with the dppe and tripod cobalt carbonyl hydrides, metallacycle product formation was evident even at short reaction times with insertion/hydrogenation ratios of 1:1, showing that using less electron-rich, steric bulky ligands prevented the bimolecular Co dimer formation, but left enough room for binding a second equivalent of TFE for metallacycle formation. Finally, Chapter 5 summarizes the findings of this Thesis and discusses future directions based on this work.
Keywords: Perfluorometallacycle; Hydrofluorocarbon; Iron; Cobalt; Activation; Hydrogenolysis; Carbene; Fluorine; Hydride; Phosphine